2022
DOI: 10.9734/ijpss/2022/v34i232604
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Selection Criteria for Some Barley Genotypes under Different Water Stress Treatments

Abstract: Nowadays, water scarcity is a great danger to agriculture development, in semiarid and arid regions beside climate change risks. Egypt is suffering from scarce water resources for agriculture; it is of high priority to rationalize irrigation water use. During two seasons, 2019/2020 and 2020/2021 the experimental were carried out to investigate the effect of three different irrigation water treatments (I1 at 45, I2 at 60 and I3 at 75% depletion of available soil moisture) on some photosynthetic, agronomical, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Under salinity stress, the other genotypes were deemed tolerable and moderately tolerant. Mariey et al [ 58 ] who confirmed that the decrease in grain yield was caused by a decrease in yield components, reported similar results. According to Mariey et al [ 58 ], grain yield is the result of the action and interaction of numerous environmental, agronomical, and physiological variables.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Under salinity stress, the other genotypes were deemed tolerable and moderately tolerant. Mariey et al [ 58 ] who confirmed that the decrease in grain yield was caused by a decrease in yield components, reported similar results. According to Mariey et al [ 58 ], grain yield is the result of the action and interaction of numerous environmental, agronomical, and physiological variables.…”
Section: Discussionmentioning
confidence: 59%
“…Mariey et al [ 58 ] who confirmed that the decrease in grain yield was caused by a decrease in yield components, reported similar results. According to Mariey et al [ 58 ], grain yield is the result of the action and interaction of numerous environmental, agronomical, and physiological variables. High NaCl content lowers plant water potential, which lowers water flow into fruit and slows the rate of fruit expansion, which could account for the decreased yield [ 59 ].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation